Authenticity: The link between destination image and place attachment - Jiang, Y.; Ramkissoon, Haywantee; Mavondo, F.; Feng, S. (Routledge, 2017)
This study explores the relationships between destination image, existential authenticity, and different dimensions of place attachment in the nature-based tourism context. A visitor-centric model is proposed in which existential authenticity is the principal mechanism that links destination image to different dimensions of place attachment. Data was collected in a survey of international visitors to two popular nature-based tourism destinations in Australia. The results indicate (a) a positive and significant effect of destination image on existential authenticity; (b) a positive and significant effect of existential authenticity on place dependence, place identity, place affect, and place social bonding; and (c) a significant mediating effect of existential authenticity in the relationship between destination image and each of the four dimensions of place attachment. The implications of this study for academics, tourism authorities, and destination marketing managers are discussed.